The long-run impact of bank credit growth on social and economic inequalities in Morocco evidence from the Johansen's cointegration analysis - KHATTAB, AHMED (The European Journal of Applied Economics, 2021)
The subject of the economic and social inequalities growth has become a major concern for economic researchers around the world. As a result, there is a great attention and concern about the significant costs of rising inequalities on peace and social coherence in society. To counteract the harms of these inequalities, Morocco has undertaken several reforms, including the implementation of a new development model set up in 2018. The main objective of this article is to estimate the impact of bank credit growth on the increase of economic and social inequalities in Morocco. In other words, we have verified whether there is a positive impact on the rise of income inequalities in Morocco. For this reason we tested, in this study, an econometric model, using the cointegration method, particularly, the error correction model. Thus, our results confirms that the degree of trade openness, bank credit and gross domestic product per capita are considered as determinants of the equilibrium of the Gini index in the long run. We used annual data covering the period 1990-2019 from the Central Bank of Morocco (BAM) database and the World Bank database (WBD). A wide range of studies demonstrate the significant positive impact between bank credits and income inequalities.
Keywords: Income inequalities, bank credits, economic growth, trade openness, cointegration.